KEMAMPUAN MENGGUNAKAN MAJAS PERBANDINGAN DALAM PRODUKSI TEKS EKSEMPLUM SISWA SMP KELAS IX LOMBOK UTARA - Ni Luh Suriati; Mahsun Mahsun; Sudirman Sudirman (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2018)
This study investigates how the nineth graders of SMP in Lombok Utara apply exemplum teks in writing expressions.  Two SMPN in Gangga and Bayan in Lombok Utara city were assigned as the research setting. An amount of 30 students and one teacer in each school was selected as participants. Of three states SMP in Lombok Utara, both schools have applied The 2013 Curriculum, so that both schools were seected as the research setting. Data were collected through written test the students made in exemplum, interviews with teachers to know strategies to express the exemplum.  The study reveals that the nineth graders of SMP in Lombok Utara perform succesfully to use figurative language for comparison. The mastery is colored as: of 58 students, 48 (79%) are succesful to use figurative language for comparison, 28% use incomplete text structure of exemplum emphasizing on orietnation and incidents.  The students have produced conjunctions, that include: conjunction intersentences, conjunction intra-sentences, and appropriate adverbs.  However, conjunctions to link paragraphs after another are short.  Exemplum that refers to example, story, or annecdote is not well developed by students.